Tit for tat? A study on the relationship between work connectivity behavior after-hours and employees’ time banditry behavior - Li, Jingya; Chen, Hao; Wang, Liang; Bao, Jiaying (Frontiers in Psychology, 2024)
Based on Conservation of Resources Theory, this study tries to reveal the mechanism of action of work connectivity behavior after-hours triggering employees' time banditry behavior. The analysis of 429 leader-employee paired data collected in three stages reveals that work connectivity behavior after-hours has a positive effect on work alienation and psychological distress. Work alienation and psychological distress mediates the relationship between work connectivity behavior after-hours and employees' time banditry behavior, respectively. In addition, organization-based self-esteem mitigates the positive effects of work connectivity behavior after-hours on work alienation and psychological distress, which in turn also moderates the indirect effects of work connectivity behavior after-hours on employees' time banditry behavior through work alienation and psychological distress, respectively.